Melacak Skeptisisme dalam Islam Klasik - Syarifuddin Syarifuddin (UIN Sunan Kalijaga Yogyakarta, 2022)
The skepticism referred to in this paper is different from the skepticism commonly known in ancient Greece. Skepticism in Islam is never isolated, but rather is a key reference point where theological questions are debated endlessly. For centuries, Muslim scholars have faced puzzling questions of a theological and philosophical nature. Their inability to answer such questions requires a paradigm shift in a new approach to religious thought. This research is intended to track how skepticism is in classical Islam, by using descriptive methods as well as historical analysis. In this study, it was found that skepticism in classical Islam became an approach in scientific and religious studies as well as a tool for scientific discipline systems test, even though skepticism was not fully institutionalized or became a form of flow. Previously, the study of skepticism in classical Islam was only limited to the thoughts of one figure, so this paper takes several case studies of figures. Skepticism in classical Islamdivided into four periods, starting from the ninth century to the twelfth century. The ninth century was marked by debates about the position of God by anthropomorphic groups with the Jahmiyah. The tenth century was marked by debates and mutual claims of truth between religions. The eleventh century was marked by al-Ghazali's critics on philosophers. Then the twelfth century was marked by Ibn Taimiyah's critics on logic, Christianity and Sufism.